2011
DOI: 10.1007/s11418-011-0542-x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro screening for antihyperlipidemic activities in foodstuffs by evaluating lipoprotein profiles secreted from human hepatoma cells

Abstract: We screened the antihyperlipidemic effects of seven edible plants by evaluation of the triglyceride (TG) and cholesterol profiles secreted from HepG2 cells. We found that the water- and ethanol-extracts of Brasenia schreberi at 100 μg/ml exhibited strong inhibitory activities against TG and cholesterol secretions from HepG2 cells stimulated with sodium oleate. Real-time RT-PCR analysis demonstrated that ethanol extract of B. schreberi (BSET) attenuated the expression of the sterol regulatory element binding pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…LipoCULTURE by Skylight Biotech Inc. A novel screening system for antidyslipidemic agents using cultured cells has been reported by Takahashi et al 75 .…”
Section: Principles and System Configuration Of The Liposearch Systemmentioning
confidence: 99%
“…LipoCULTURE by Skylight Biotech Inc. A novel screening system for antidyslipidemic agents using cultured cells has been reported by Takahashi et al 75 .…”
Section: Principles and System Configuration Of The Liposearch Systemmentioning
confidence: 99%
“…It was previously reported that ethanol and water extracts of Brasenia schreberi exhibit strong inhibitory activities against triglyceride and cholesterol secretions from human hepatoma cells [22], although the inhibitory compound has not yet been purified and identified. There is no such report for Petasites japonicus; as far as we know, Rosa species contain polyphenolic compounds with antioxidant activities [12].…”
Section: Rt Inhibition By Extracts Of Edible Flowersmentioning
confidence: 99%
“…To assess a role of FAS in regulating liver steatosis by miR-130a-3p, we investigated the effects of miR-130a-3p on SO-induced steatosis (29) in HepG2 cells. Overexpression of miR-130a-3p significantly prevented SO-increased TG content in these cells compared with control cells (Fig.…”
Section: Overexpression Of Mir-130a-3p Reverses Liver Steatosis In Dbmentioning
confidence: 99%